Research in progress: Learning from adopters and resisters of e-learning in New Zealand polytechnics and institutes of technology - Hugh Barr; Stephen Bright; John Clayton; Stephen Cox; Beverley Gower; David Mitchell (Flexible Learning Association of New Zealand, 2012)
The exponential growth of e-learning practices in higher education has resulted in an increasing interest in the ways in which faculty members in tertiary institutions perceive e-learning and the ways in which they apply e-learning in their courses. Faculty who might be described as "innovators" or "early adopters" have generally embraced e-learning enthusiastically; other faculty remain disengaged or disinterested. Disengagement may be due to faculty concerns about access to technology, software, and networks or it may stem from concerns about time allocations and staff support. Disinterest may be due to a perceived lack of relevance of e-learning strategies to particular courses, or it may simply reflect faculty members' dispositions to change, innovation, and adoption. The project briefly described in this paper seeks to determine the causes of disengagement and disinterest in the adoption of e-learning approaches among teaching faculty.